Analisis Ketidakseimbangan Beban Pada Transformator Distribusi di PT. PLN (Persero) Ulp Bangli - Yasa, I Wayan Sugara; Wirajaya, Agung; Adrama, I Nyoman (Universitas Medan Area, 2024)
This research basically started from a gradual power outage carried out by PLN. From this power outage, it is very troubling for the community, both industry and household customers. Load imbalances on electric power distribution transformers always occur and these imbalances occur due to unequal use of electrical energy. As a result of the imbalance of the load, current flows in the neutral transformer. The current flowing in the neutral conductor of this transformer causes losses, namely losses due to neutral current in the neutral conductor of the transformer. The losses contained in the transformer are power loss, core loss and copper loss. In analyzing problems using mathematical models include equations of transformer load imbalance, power losses and efficiency. After analysis, it shows that the transformer is in an unbalanced state where if there is a large load imbalance, the neutral current that appears is also large. The efficiency of the transformer will be even greater if the difference between the inlet and outlet power is small. The power loss occurred 1.98533 kW and the efficiency was 97.06%.